PERTANIAN PERKOTAAN : URGENSI, PERANAN, DAN PRAKTIK TERBAIK - Ahmad Rifqi Fauzi; Annisa Nur Ichniarsyah; Heny Agustin (JURNAL AGROTEKNOLOGI, 2016)
As the cities become more attractive to people, it is predicted that in 2020 there will be around 75% of population live in the cities. The direct effects include the increase of city burden due to the poor, the jobless, and the lack access to food. The answer of the problems above could come from urban farming. A number of studies have cited that urban farming are not only solving the problem of access and food availability but also creating new job opportunities and reduce the poverty. The best practices of urban farming have developed in some countries. The case study in Africa shows that urban farming can supply 15-20% of household needs and increase the income up to 27%. Similar results are also found in Asia, America, and Europe, even though each region faces different challenges and barriers. The success of urban farming reaffirm the important roles of agriculture in improving human’s quality. Urban agriculture in Indonesia have started to develop after economic crisis at 1997 and growing rapidly since 2011 with the emergence of communities gardening in the 33 cities and 9 university. But, the development of urban agriculture in Indonesia have barriers include low levels of community participation, extensive land holdings were small, and the lack of government support.Keywords : best practice, role,urban agriculture, urgency